(untitled) (Medico Legal Update, 2020)
A observational study to examine the association of Health related behaviours and Body mass index among young adults at selected colleges in Kanchipuram District, Tamil Nadu, India’’. The objectives were to examine the lifestyle practices and Body mass index among young adults at Kanchipuram district, Tamil Nadu and to find out the association between lifestyle practices and BMI with demographic variables. The convenience sampling was used to select 100 young adults. The data collection tools were validated and reliability was established. The data were collected by self-administered questionnaire. The collected data was Tabulated and Analyzed. Descriptive and Inferential statistical methods were used. The study shows that of the higher frequency of 18-24 years (96%) and lower frequency of 20-24 years (4%). In Gender, Male is lowest frequency (28%) and Female is the highest frequency (72%). There was significant association between the knowledge and the selected demographic variables.